Global forest resources assessment 2010 : (Food and Agriculture Organization of the United Nations, 2010)
This publication (FRA 2010) is the most comprehensive assessment of forests and forestry to date - not only in terms of the number of countries and people involved, but also in terms of scope. it examines the current status and recent trends for about 90 variables covering the extent, condition, uses and values of forests and other wooded land, with the aim of assessing all benefits from forest resources. Carried out at five-years intervals, FRA provides the data and information needed to support policies, decisions and negotiations in all matters where forests and forestry play a part. Statistics on trends in forest carbon stocks. FRA 2010 also includes information on variables such as forest health, The contribution of forests to national economies And The legal and institutional framework governing the management and use of the world's forests.